ISSUES OF INTERNALLY DISPLACED PERSONS: A BRIEF RESPONSE OF INDIA - Siddiqui, Shazia; Singha, Sukanya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The astounding numbers of 47 million new internal displacements tell a harrowing tale as the planet grapples with conflicts and disasters," stated Ugochi Daniels, deputy director general of the International Organization for Migration (IOM). "This report is a stark reminder of the urgent and coordinated need to expand disaster risk reduction, support peacebuilding, ensure the protection of human rights and whenever possible, prevent the displacement before it happens.